Rhinosporidiosis - A Case Report - Rao, N Sudarshan; Prasad, D L N; Reddy, D Venkata Raghava (Indian Journal of Plastic Surgery, 1994)
A case of Rhinosporidiosis with an unusual feature of origin in the lower eyelid with spread to the naso-maxillary area and chronicity of 22 years is presented.